Uwagi o budownictwie obronnym arcybiskupów gnieźnieńskich - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
The subject of the present paper are the remarks on the defending constructions of the Gniezno archbishops. Great properties consisting - at the break of the middle ages and modern times - of more than 300 villages and towns, as well as a significant role of the Gniezno archbishops in the Polish state, represented a sufficient basis enabling to build the defending constructions. In former literature the archiepiscopal castles were known only in Gniezno, Kamień Pomorski, Łowicz, Opatówek, Uniejów and in Źnin-Wenecja. The first five castles were erected by abp Jarosław Bogoria Skotnicki in the middle or 3rd quarter of 14th century, the latter was the knight's foundation bought by the archbishops in the 1st quarter of 15th century. There is not satisfactory state of investigations of the archiepiscopal castles as far as both the source-research and the field archaeological and architectonical investigations are concerned. That is clearly illustrated by a situation of Skierniewice, where the archiepiscopal palace still exists. It seems that the earlier archiepiscopal construction in Skierniewice was a castle erected in the middle of 15th century by archbishops Jan Sprowski on the isle surrounded by the moat. This castle, known from the incomplete archival data, was destroyed or rebuilt in the 1st half of 17th century. The Skierniewice example shows that the investigations of the archiepiscopal castles have not excesses – an inventory stage. The small and not existing presently defending constructions erected in the centers of particular demesnes are also forgotten. The paper concerns the formerly unknown manors in Kurzelów and Piątek. They (as well as the mentioned manors in Zychów, Łęgonice and Marchwacz) were small dwelling houses, sometimes a tower, accompanied by several household constructions, situated an the mounds and surrounded by meats. The essential function of. the archiepiscopal manors in question was, beyond any doubt, the dwelling purpose. They were inhabited by the administrators of properties, and periodically they played a role of the residence for archbishops travelling around the country. Besides the residential and administrative role the objects in question used to perform also the defending tasks, guarding the security of the inhabitants and material goods collected by the archibishops. The defending manors founded in the middle ages survived untill the 17th century, being frequently restored and rebuilt. It seems that here appears an urgent need to investigate - by means of archaeological methods - at least few defending archiepiscopal manors for the date enabling one to compare this kind of "rural defending seats" with the defending constructions erected by the secular feudals are missing. It seems moreover, that the investigations of the small archiepiscopal seats should be carried out in a close collaboration between the historian-expert in written sources and the field explorers-archaeologist and architect.